Genetic and Cytological Analyses of the Natural Variation of Seed Number per Pod in Rapeseed (Brassica napus L.) - Yang, Yuhua; Wang, Ying; Zhan, Jiepeng; Shi, Jiaqin; Wang, Xinfa; Liu, Guihua; Wang, Hanzhong (Frontiers in Plant Science, 2017)
Seed number is one of the key traits related to plant evolution/domestication and crop improvement/breeding. In rapeseed germplasm, the seed number per pod (SNPP) shows a very wide variation from several to nearly 30; however, the underlying causations/mechanisms for this variation are poorly known. In the current study, the genetic and cytological basis for the natural variation of SNPP was firstly and systematically investigated using the representative four high-SNPP and five low-SNPP lines. The results of self- or cross-pollination experiment between the high- and low-SNPP lines showed that the natural variation of SNPP was mainly controlled by maternal effect (mean=0.79), followed by paternal effect (mean=0.21). Analysis of the data using the diploid seed embryo-cytoplasmic-maternal model further showed that the maternal genotype, embryo and cytoplasm effects respectively explained 47.6%, 35.2% and 7.5% of the variance. In addition, the analysis of combining ability showed that the SNPP of hybrid F1 was mainly determined by the GCA of parents (63.0%), followed by the SCA of parental combination (37.0%). More importantly, the cytological observation showed that the SNPP variation between the high- and low-SNPP lines could be attributable to the accumulative differences in its components. Of these, the number of ovules, the proportion of fertile ovules, the proportion of fertile ovules to be fertilized and the proportion of fertilized ovules to develop into seeds accounted for 30.7%, 18.2%, 7.1% and 43.9%, respectively. The accordant results of both the genetic and cytological analyses provide solid evidences and systematic insights to further understand the mechanisms underlying the natural variation of SNPP, which will facilitate the development of high-yield cultivars in rapeseed.